Reconstruction of Ali Yafie's Thinking in the Field of Social Fiqh in the Development of Islamic Law (Critical Review) - Amrin, Amrin; Suciyani, Suciyani; Nurrahmaniah, Nurrahmaniah (Fakultas Syariah INSURI Ponorogo, 2023)
This study aims to multiply Ali Yafie's thoughts on the development of Islamic law in Indonesia. This research uses qualitative research with a literature study approach. The data collection techniques use the library research, namely: trying to collect data from books or literature related to the researcher's discussion. The data analysis uses deductive analysis with interpretative. The results of the study show that Ali Yafie's thoughts in the field of social fiqh try to understand Islamic teachings, at least with several approaches, namely: Combining Text/nash with Reason, Blending Text with reality, and combining text with Maslahah makes fiqh more contextual and directs it more towards issues of a more social nature. in the dynamic development of Islamic law in Indonesia.